Majocchi's Granuloma with Epidermal Cysts due to Trichophyton rubrum: Ultrastructural Observations - Naomi Tani; Nanako Yamada; Kazushi Anzawa; Takashi Mochizuki; Osamu Yamamoto (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)